2005
DOI: 10.1345/aph.1g180
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacy–Based Pharmaceutical Care for Asthma Patients

Abstract: The study shows that PC for people with asthma has a positive impact on humanistic and, to some extent, on clinical outcomes. To determine potential economic benefits, future research should focus on patients with more severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
93
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 27 publications
5
93
0
7
Order By: Relevance
“…These factors have already been shown to be an important barrier to the achievement of good asthma control, as prescribing an appropriate asthma control treatment may not be successful when the patient uses the medication inappropriately [6][7][8][9]. Only a few well-designed studies have investigated the effect of pharmacist care on asthma patients to date [10][11][12][13][14][15]. These studies have shown improvements in peak flow [12][13][14][15], asthma severity [10,13], symptom scores [11], drug utilisation [10,[12][13][14] and humanistic outcomes (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These factors have already been shown to be an important barrier to the achievement of good asthma control, as prescribing an appropriate asthma control treatment may not be successful when the patient uses the medication inappropriately [6][7][8][9]. Only a few well-designed studies have investigated the effect of pharmacist care on asthma patients to date [10][11][12][13][14][15]. These studies have shown improvements in peak flow [12][13][14][15], asthma severity [10,13], symptom scores [11], drug utilisation [10,[12][13][14] and humanistic outcomes (e.g.…”
mentioning
confidence: 99%
“…Only a few well-designed studies have investigated the effect of pharmacist care on asthma patients to date [10][11][12][13][14][15]. These studies have shown improvements in peak flow [12][13][14][15], asthma severity [10,13], symptom scores [11], drug utilisation [10,[12][13][14] and humanistic outcomes (e.g. quality of life, asthma knowledge) [10,[12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36 This is unfortunate, as many studies have demonstrated the effectiveness of pharmacist delivered PC services with regard to clinical, humanistic, and economic outcomes in different disease conditions. [37][38][39] More initiatives must be executed to educate Qatar's population about the importance of PC and to promote the pharmacist's role through media campaigns and increased support from Qatar's Supreme Council of Health.…”
mentioning
confidence: 99%
“…Finally, in 2013, was proposed the definition of pharmaceutical care as a pharmacist's contribution to the care of individual patients, leading to optimize the use of drugs and improve health outcomes [7,8]. In the practice pharmaceutical care is realized by a range of services provided by pharmacists to patients, particularly suffering from chronic diseases.…”
Section: The Pharmaceutical Carethe Development Of Servicesmentioning
confidence: 99%